2018
DOI: 10.1021/acs.jpcc.8b03757
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charge Transfer and Relaxation Dynamics in Polymer-Encapsulating Single-Walled Carbon Nanotubes: Polythiophene and Coronene Polymer

Abstract: We investigate the photophysical properties of polymer-encapsulating single-walled carbon nanotubes (SWNTs) using absorption spectroscopy, photoconductivity spectroscopy, and femtosecond pump−probe spectroscopy. In a polythiophene (PT)-encapsulating SWNT film, one or two PT layers are encapsulated within SWNTs, depending on the tube diameter. For single encapsulated PT layers, the photoconductivity action spectrum shows a large photocurrent signal corresponding to absorption bands associated with PT exciton an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Yet, in some other cases, coronene was found to build ordered and disordered packings in the carbon nanotubes, [185–186] resulting in graphene nanoribbons, [187] inner tubes, peapods [188] and others, depending on the conditions used to incorporate coronene in nanotubes. The ultrafast charge transfer and relaxation dynamics of polythiophene and coronene polymer‐encapsulated nanotubes have been studied, [189] while coronene molecules in carbon nanotubes [190] also offer a high charge carrier mobility of 14.93 cm 2 V −1 s −1 . In other studies, coronene composites with carbon nanotubes showed a bright photoluminescence [191] …”
Section: Resultsmentioning
confidence: 99%
“…Yet, in some other cases, coronene was found to build ordered and disordered packings in the carbon nanotubes, [185–186] resulting in graphene nanoribbons, [187] inner tubes, peapods [188] and others, depending on the conditions used to incorporate coronene in nanotubes. The ultrafast charge transfer and relaxation dynamics of polythiophene and coronene polymer‐encapsulated nanotubes have been studied, [189] while coronene molecules in carbon nanotubes [190] also offer a high charge carrier mobility of 14.93 cm 2 V −1 s −1 . In other studies, coronene composites with carbon nanotubes showed a bright photoluminescence [191] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the molecules are closely attached to the surfaces of the SWNTs on either the inside or outside. As pointed out in ref , the van der Waals bonding between the SWNT and the wrapping molecule has a similar nature to that between the SWNT and the encapsulated molecule. Theoretical calculations showed that ionization potentials of PT molecules on the inside of SWNTs with diameters of 0.9–1.7 nm were about 0.1 eV larger than that of the isolated PT .…”
Section: Resultsmentioning
confidence: 67%
“…In a recent work, Nakamura et al have studied the photoexcitation spectrum of a coronene polymer encapsulated in a carbon nanotube . In this work, they show that two absorption bands (at around 1.7 and 3.4 eV) are due to a charge transfer from the coronene polymer to the nanotube.…”
Section: Resultsmentioning
confidence: 92%